2002
DOI: 10.1177/154405910208100711
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Properties of Ground Y-TZP-Zirconia Ceramics

Abstract: Yttria-stabilized zirconia ceramics is a high-performance material with excellent biocompatibility and mechanical properties, which suggest its suitability for posterior fixed partial dentures. The hypothesis under examination is that the strength and reliability of Y-TZP zirconia ceramics are affected by the inner surface grinding of crowns, and vary with the grinding parameter. Flexural strength, surface roughness, and fracture toughness were determined on samples machined by face and peripheral grinding wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
0
28

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(234 citation statements)
references
References 6 publications
8
198
0
28
Order By: Relevance
“…This result agreed with the results of previous studies which reported higher bond strengths with the use of MDPbased primer 8,42) . This could be due to the capability of acidic functional monomer MDP reacting with the substrate [13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result agreed with the results of previous studies which reported higher bond strengths with the use of MDPbased primer 8,42) . This could be due to the capability of acidic functional monomer MDP reacting with the substrate [13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike conventional dental ceramics, high-strength ceramics such as yttria-tetragonal zirconia polycrystal (Y-TZP) have high crystalline content and comprise many crystalline filler particles without a glass phase at the crystalline border 13) . Therefore, these ceramics are not suitable for acid etching 8,[14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, CAD/CAM production has clearly expanded the palette of materials for dental prosthe ses by providing access to new ceramic materials with high dependability. 15,[28][29][30][31] The stability values of zirconium oxide ceramics permit, in many areas of indi cation, the use of this material as an alternative to metal frames for perma nent prostheses. 30 The production of long-term temporary prostheses has, as a result of the use of a virtual wax up on the computer, become faster, more convenient and more pre dictable.…”
Section: Significance For the Dentistmentioning
confidence: 99%
“…For zirconia, the ground surface will show under XRD a localized phase transformation, which involves an increased resistance to crack propagation. Nevertheless, depending on the diamond grit size and shape and the time-dependence of the applied forces, deep reaching surface cracks will show both a reduction in strength and reliability [4][5][6][7][8][9][10]. Grinding dense alumina will also induce surface residual compressive stresses which can enhance the average strength, but increasing the depth of cut will produce machining flaws in form of surface cracks penetrating deeper than the surface compressive layer lowering the reliability and strength [11,12].…”
Section: Results 3y-tzp Wasmentioning
confidence: 99%